ANALYSIS OF CHARACTER VALUES IN THE TRADITIONAL GAMES COLLECTION OF SEREN TAUN CUSTOM RITUALS: AN ETNOGRAPHIC STUDY - Praramdana, Gilang Kripsiyadi; Nugraha, Febby Fajar (PrimaryEdu : Journal of Primary Education, 2020)
Character education has a major aim to develop quality and excel the human resources. It is based on the Republic of Indonesia's National Education Objectives. The values of this nation's character education are embedded in the ancestral heritage, one of them is a traditional game. The descriptive-analytic method with an ethnographic approach that we used in this study was to analyze and describe the phenomena. Therefore, we chose the Spradley ethnographic method (cognitive anthropology) as a method with phased progressive research (The Developmental Research Sequence). Based on 15 traditional games in the Ritual AdatSerenTaun in Cigugur, we have classified potential major character values which include: (1) five (33%) types of games have independent major character values; (2) seven (46%) types of games have gotongroyong major character values; and (3) four (27%) types of games have integrity major character value. While both religious and nationalist major character values have not been found based on our analysis of 15 types of games in this study.